Home grown; home inspired: the resilience of traditional hand built pottery production in ijaye, Abeokuta, Southwest Nigeria (2021)
Despite foreign influence and westernisation, the art of traditional hand built pottery persists in some communities across Nigeria. This study conducted in Ijaye, Abeokuta, South-West Nigeria examined the factors responsible for the resilience of simple hand built pottery production. In-depth interviews of potters and residents of Ijaye were used to collect data on the relevance of traditional pottery in terms of production and usage. The interviews were transcribed and analysed using content analysis. Findings indicated that in contemporary times, the pottery wares were used both for traditional and religious practices. Also, the low cost of the wares encouraged its use. The paper concluded that pottery made in Ijaye served as rich cultural portrayals, had economic provisioning, performed religious functions and aesthetic purposes for awide range of people across all levels of the society.